A serial mediation model testing growth mindset, life satisfaction, and perceived distress as predictors of perseverance of effort. (1st December 2020) - Lam, Kelly Ka Lai; Zhou, Mingming
Abstract: Recent studies have consistently lent support for the significant association between growth mindset and perseverance of effort; however, only a handful of studies focused on examining the potential mediators in this association. The current study examined the mediating role of life satisfaction and perceived distress in the relationship between growth mindset and perseverance of effort. A total of 377 undergraduate students responded to an online survey package. Structural equation modeling results showed that growth mindset, life satisfaction, perceived distress were significantly associated with perseverance of effort. Moreover, a serial mediation was found among the variables: students with a growth mindset tended to report higher general life satisfaction, which further decreased perceived distress level, and subsequently weakened perseverance of effort. Theoretical and practical implications were discussed. Highlights: Growth mindset was positively associated with perseverance of effort. Growth mindset was related to life satisfaction, but not perceived distress. Life satisfaction and perceived distress affected perseverance of effort. A serial mediation model was found among these variables.